New side chain cholesterol-functionalised aliphatic polycarbonate copolymer: synthesis and phase behaviour. Issue 9 (15th July 2017) - Liu, Xiao-Feng; Xu, Xiao-Xu; Li, Qun; Hu, Jian-She; Yang, Li-Qun; Chen, Qi-Fan; Lu, Yan-Hua
ABSTRACT: A new side cholesterol-functionalised liquid crystal (LC) copolymer based on aliphatic polycarbonate backbone was synthesised. The chemical structures of the block copolymers obtained in this study were characterised with Fourier Transform Infrared Spectroscopy (FT-IR) and Proton Nuclear Magnetic Resonance ( 1 H NMR) spectra. Their thermal stability and phase behaviours were investigated with thermogravimetric analysis (TGA) measurements, differential scanning calorimetry, and polarising optical microscopy. The molecular organisation in the mesophase was studied by temperature-dependent X-ray diffraction (XRD). As a result, the block copolymer bearing side cholesteryl groups showed a glass transition at 15.8°C and a smectic A (SmA) to isotropic phase transition at 151.3°C on heating cycle. XRD indicated that the block LC copolymer showed an interdigitated molecular arrangement of the mesogenic units within the smectic layers. This partial bilayer structure was similar to the SmA phase formed by polar mesogens. Graphical Abstract: